Faktor-Faktor Yang Mempengaruhi Produksi Usahatani Padi Sawah Di Desa Mogoyunggung Satu Kecamatan Dumoga Timur Kabupaten Bolaang Mongondow - Tumundo, Andreas Michael; Rori, Yolanda Pinky Ivanna; Loho, Agnes Estephina (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the factors that influence the production of paddy rice farming in the village of Mogoyunggung Satu, Dumoga Timur District, Bolaang Mongondow Regency. This research was conducted from October to December 2021. The method used in this research is quantitative descriptive analysis. The types and sources of data used in this study were primary data and secondary data. The sampling method used the simple random sampling method. The data were analyzed using the Cobb Douglas model regression analysis. , phonska fertilizer and labor have a significant effect on the production of lowland rice farming in Mogoyunggung Satu Village, Dumoga Timur District, Bolaang Mongondow Regency 38,699 with a significance of 0.000. Partially, seeds, urea fertilizer, and phonska fertilizer have a significant effect on the production of lowland rice farming. While land area and labor do not significantly affect the production of lowland rice farming. The coefficient of determination (R2) contributed by the factor of land area, seeds, urea fertilizer, phonska fertilizer and labor contributed 86.2% to the model formed while the remaining 13.8% was influenced by other factors not examined in this study.